Achieving sustained competitive advantage in retail and consumer service firms: The role of entrepreneurial orientation and entrepreneurial bricolage - Tajeddini, Kayhan; Gamage, Thilini Chathurika; Tajdini, Javad; Qalati, Sikandar Ali; Siddiqui, Faiza (Elsevier Sci Ltd, 2023)
The vital role of entrepreneurial orientation and entrepreneurial bricolage in creating sustained competitive advantage in retail and consumer service firms is increasingly acknowledged in modern markets. Using data from 246 retail and consumer service firms (hereafter R & CSFs) in Japan, this paper develops and empirically tests a framework delineating how entrepreneurial-oriented R & CSFs strategically combine existing resources while managing risks to differentiate their service portfolios to be competitive. The findings reveal that entrepreneurial orientation and entrepreneurial bricolage influence differentiation advantage and risk management, which, in turn, is associated with creating a sustained competitive advantage (hereafter SCA). This paper adds novel insights to the dynamic capabilities view and retail and service marketing literature by identifying entrepreneurial orientation, entrepreneurial bricolage, and risk management as dynamic capabilities, which allows R & CSFs to create service innovations in resource-constrained environments.
Keywords: Differentiation advantage; Entrepreneurial bricolage; Entrepreneurial orientation; Sustained competitive advantage